Enhanced ACL Graft Incorporation by Novel Minimally Invasive Activation of Endogenous Stem Cells. Issue 7 (21st July 2017) - Kremen, Thomas J.; Bez, Maxim; Giaconi, Joseph C.; Tawackoli, Wafa; Avalos, Pablo; Sheyn, Dmitriy; Snedeker, Jess G.; Gazit, Zulma; Pelled, Gadi; Gazit, Dan
Objectives: The ultimate healing of a ligament graft to bone is a lengthy process that results in reparative tissue that is distinctly different from a native ligament insertion. This known structural aberration results in inferior biomechanical properties and can contribute significantly to recurrent injury as well as compromised function. Thus, technology allowing for accelerated biologic incorporation as well as the recapitulation of a native insertion would be of great benefit to patients. We hypothesized that the treatment of anterior cruciate ligament (ACL) reconstruction bone tunnels with bone morphogenetic protein (BMP) DNA combined with a pulse of ultrasound (US) energy would lead to activation of endogenous stem cells and result in enhanced graft incorporation. Methods: Soft tissue allograft ACL reconstruction was performed in nine mini-pigs using cortical screw post fixation. A collagen scaffold was added to the terminus of each tendon graft limb contained within the corresponding bone tunnel. On post-operative day 14, a lipid microsphere solution containing DNA encoding either green fluorescence protein (GFP, n=3 pigs) or BMP-6 (n=6 pigs) was delivered into the bone tunnels percutaneously under fluoroscopic guidance. The bone tunnels in the US treated group were then immediately treated with a transcutaneous US energy pulse at the site of the bone tunnels, whereas the control group did not receive US delivery. At five days post-treatment the cells occupying the bone tunnels of the GFP treated pigs (n=3) were harvested and subjected to fluorescence-activated cell sorting (FACS) analysis to assess for expression of GFP as well as known mesenchymal stem cell (MSC) markers (CD29, CD44, CD90). Six weeks post-treatment the BMP/US treated pigs (n=3) and control pigs (n=3) were sacrificed and their knee joints were scanned using microCT. Biomechanical testing of anterior-posterior (AP) knee laxity was performed via application of sinusoidal AP-directed shear loads for 12 cycles. Load to failure was assessed by removal of the joint capsule, menisci, collateral ligaments, and the PCL leaving only the ACL graft intact. The tibia and femur were then mounted on a universal material testing machine with a 5kN load cell and distracted until failure of the ACL graft or graft-bone interface. Results: FACS analysis done 5 days after GFP gene delivery showed that 40-50% of the cells occupying the US treated bone tunnels expressed GFP and this was significantly more than the cells in untreated bone tunnels (p< 0.05). In addition, 12-22% of the cells in the bone tunnels expressed MSC markers. Quantification of bone volume in ACL reconstruction tunnels showed significantly higher values in BMP-6/US treated animals (fig 1A, B, C; *p<0.05, t-test). AP laxities at ±20N of BMP-6/US treated pigs were lower than untreated pigs (fig 1D). The linear stiffness (fig 1E) and maximum load to failure (fig 1F) were both significantly higher than untreated pigs, demonstrating stronger graft-bone integration among the treated animals. (*p<0.05, t-test). Conclusion: Endogenous stem cell gene expression can be altered in a large animal model via novel minimally invasive techniques and this can result in enhanced ligament biomechanical properties. Minimally invasive biologic technology such as this would likely be of significant benefit to the treatment of patients undergoing ligament reconstruction procedures and more research regarding these technologies is certainly warranted.